It’s A Two-Way Street: The Joint Meaning of Illocutionary Acts of Arguing - Haro Marchal, Amalia (Informal Logic, 2025)
As a communicative activity, argumentation has been characterized as a specific type of speech act. In the analysis of the speech act of arguing, I have distinguished two illocutionary levels: one related to the speaker’s utterance and the other related to the communicative exchange involving the speaker and the interlocutor. In this article, I argue that these two levels are associated with the speaker’s meaning and the joint meaning, respectively. The two-level analysis of meaning makes it possible to account for cases in which commitment attributions are at stake and that may, as a result, give rise to a special form of discursive injustice.